2020
DOI: 10.1055/s-0040-1721145
|View full text |Cite
|
Sign up to set email alerts
|

DAPT Score to Stratify Ischemic and Bleeding Risk after Percutaneous Coronary Intervention: An Updated Systematic Review, Meta-Analysis, and Meta-Regression of 100,211 Patients

Abstract: Letter to the Editor 687This document was downloaded for personal use only. Unauthorized distribution is strictly prohibited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…After its development in the DAPT trial, the DAPT score has been extensively investigated with regard to its ability to stratify ischemic risk in a wide variety of patient groups who have received PCI (8)(9)(10)(11). Most of the studies confirmed that patients with a high DAPT score have a higher incidence of ischemic events when compared with patients with a low DAPT score.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After its development in the DAPT trial, the DAPT score has been extensively investigated with regard to its ability to stratify ischemic risk in a wide variety of patient groups who have received PCI (8)(9)(10)(11). Most of the studies confirmed that patients with a high DAPT score have a higher incidence of ischemic events when compared with patients with a low DAPT score.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with a high DAPT score (≥2), who had an increased ischemic risk, treatment with extended DAPT beyond 1 year resulted in a reduction in ischemic events but without an increase in bleeding (7). The DAPT score has been validated as useful for stratifying ischemia and bleeding risk in other patient groups, including Asian patients, outside the derivation cohort of the DAPT trial (8)(9)(10). Although there were some controversial results regarding its discriminating ability in one study (11), the DAPT score seems to be a clinically useful tool for determining DAPT duration after PCI.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Ueda et al showed that in an extensive Swedish registry, this score did not effectively discriminate between bleeding and ischemic risk [ 38 ]. In a recent analysis, including 100,211 post-PCI patients, a DAPT score ≥2 was able to accurately recognize patients at high ischemic and low bleeding risk [ 39 ].…”
Section: Residual Risk In Chronic Coronary Syndromesmentioning
confidence: 99%